From Rescue Mission to Colonial Ambitions: A Reading of Stanley's My African Travels - Upadhyay, Toya Nath (Molung Educational Frontier, 2023)
This study examines Henry Morton Stanley's My African Travels through a post-colonial lens in order to explore how Stanley’s mission of rescuing a missing explorer turns into his colonial ambitions in the interior of Africa. Primarily with a project of finding the missing missionary and explorer David Livingston by name, Stanley sets out on his African journey in 1871. But after finding Livingston, Stanley’s eyes fall upon the plenitude of natural resources and backwardness of the native people that instantly stimulate in him a sense of the possibilities of commerce and Christianization of the natives. Consequently, he makes more explorations, draws maps and fills them with names, fights the locals, and establishes stations at different locations that ultimately turn into European colonies. This study analyzes and interprets his My African Travels as a colonial discourse in that it operates as a tool for the European colonial enterprise. The study employs conceptual terms related to colonial discourse for analysis and interpretation.